Configurable Processor Architectures: History and Trends - Andrews, David; Plessl, Christian (Proc. Int. Conf. on Engineering of Reconfigurable Systems and Algorithms (ERSA))

Proc. Int. Conf. on Engineering of Reconfigurable Systems and Algorithms (ERSA)

Using Shared Library Interposing for Transparent Acceleration in Systems with Heterogeneous Hardware Accelerators - Beisel, Tobias; Niekamp, Manuel; Plessl, Christian (Proc. Int. Conf. on Application-Specific Systems, Architectures, and Processors (ASAP))

Reconfigurable Nodes for Future Networks - Keller, Ariane; Plattner, Bernhard; Lübbers, Enno; Platzner, Marco; Plessl, Christian (Proc. IEEE Globecom Workshop on Network of the Future (FutureNet))

Rupeas: Ruby Powered Event Analysis DSL - Woehrle, Matthias; Plessl, Christian; Thiele, Lothar (Proc. Int. Conf. Networked Sensing Systems (INSS))

Performance Estimation for the Exploration of CPU-Accelerator Architectures - Kenter, Tobias; Platzner, Marco; Plessl, Christian; Kauschke, Michael (Proc. Workshop on Architectural Research Prototyping (WARP), International Symposium on Computer Architecture (ISCA))

Liquid Crystal Nano-particles, LCNANOP – a SONS II Collaborative Research Project - Goodby, J. W.; Bates, M.; Saez, I. M.; Gorecka, E.; Kitzerow, Heinz-Siegfried; Guillon, D.; Donnio, B.; Serrano, J.-L.; Deschenaux, R. (Mater. Res. Soc. Symp. Proc. 1134)

Entwicklung und psychometrische Überprüfung eines Messinstruments zur Erfassung pädagogischer Kompetenzen in der universitären Lehrerbildung. - Seifert, Andreas; Hilligus, Annegret Helen; Schaper, Niclas (Lehrerbildung auf dem Prüfstand)

LEK – Längsschnittliche Erhebung pädagogischer Kompetenzen von Lehramtsstudierenden: Testinstrumente, Forschungsdesign und Fragestellungen. - König, Johannes; Seifert, Andreas; Blömeke, Sigrid; Schaper, Niclas (AEPF-Tagung „Selbstregulation – Fremdregulation“)

Welche Dimensionen bzw. Modellstruktur liegt der Messung pädagogischer Kompetenz in der universitären Lehrerausbildung zugrunde? - Seifert, Andreas; Schaper, Niclas (AEPF-KBBB-Tagung)

On global effects caused by locally noneffective unitary operations - Gharibian, Sevag; Kampermann, Hermann; Bruß, Dagmar (Quantum Information & Computation)
Given a bipartite quantum state rho with subsystems A and B of arbitrary dimensions, we study the entanglement detecting capabilities of locally noneffective, or cyclic, unitary operations [L. B. Fu, Europhys. Lett., vol. 75, pp. 1-7, 2006]. Local cyclic unitaries have the special property that they leave their target subsystem invariant. We investigate the distance between rho and the global state after local application of such unitaries as a possible indicator of entanglement. To this end, we derive and discuss closed formulae for the maximal such distance achievable for three cases of interest: (pseudo)pure quantum states, Werner states, and two-qubit states. What makes this criterion interesting, as we show here, is that it surprisingly displays behavior similar to recent anomalies observed for non-locality measures in higher dimensions, as well as demonstrates an equivalence to the CHSH inequality for certain classes of two-qubit states. Yet, despite these similarities, the criterion is not itself a non-locality measure. We also consider entanglement detection in bound entangled states.

Signatures of nonclassicality in mixed-state quantum computation - Datta, Animesh; Gharibian, Sevag (Physical Review A)
We investigate signatures of non-classicality in quantum states, in particular, those involved in the DQC1 model of mixed-state quantum computation [Phys. Rev. Lett. 81, 5672 (1998)]. To do so, we consider two known non-classicality criteria. The first quantifies disturbance of a quantum state under locally noneffective unitary operations (LNU), which are local unitaries acting invariantly on a subsystem. The second quantifies measurement induced disturbance (MID) in the eigenbasis of the reduced density matrices. We study the role of both figures of non-classicality in the exponential speedup of the DQC1 model and compare them vis-a-vis the interpretation provided in terms of quantum discord. In particular, we prove that a non-zero quantum discord implies a non-zero shift under LNUs. We also use the MID measure to study the locking of classical correlations [Phys. Rev. Lett. 92, 067902 (2004)] using two mutually unbiased bases (MUB). We find the MID measure to exactly correspond to the number of locked bits of correlation. For three or more MUBs, it predicts the possibility of superior locking effects.

Coupling Dynamics of Quantum Dots in a Liquid-Crystal-Tunable Microdisk Resonator - Förstner, Jens; Meier, Cedrik; Piegdon, Karoline; Declair, Stefan; Hoischen, Andreas; Urbanski, Mark; Meier, Torsten; Kitzerow, Heinz-Siegfried (Advances in Optical Sciences Congress)
We experimentally and theoretically investigate microdisk resonators with embedded quantum dots immersed in a liquid crystal in its nematic phase, showing the tunabililty of the photonic modes via external parameters like temperature or electric field.
Keywords: tet_topic_microdisk

Anticrossing of Whispering Gallery Modes in Microdisk Resonators Embedded in a Liquid Crystal - Förstner, Jens; Declair, S.; Meier, Cedrik; Meier, Torsten (Theoretical and Computational Nanophotonics Tacona-Photonics)
We numerically investigate Whispering Gallery Modes (WGM) in a subwavelength microdisk resonator [1] embedded in an uniaxial anisotropic liquid crystal environment. It is shown that the WGMs have anticrossing behavior when modes of different radial mode order M or azimuthal order N approach each other spectrally.
Keywords: tet_topic_microdisk

Shaping the spatiotemporal dynamics of the electron density in a hybrid metal-semiconductor nanostructure - Reichelt, Matthias; Meier, Torsten (Optics Letters)
A one-dimensional semiconductor nanostructure is locally excited through a metal aperture. It is shown that the electron density can be coherently localized at desired spatial and temporal positions by using nontrivially shaped laser pulses. To obtain the optimized laser field, Bloch equations for a tight-binding model system are solved together with a genetic pulse-shaping algorithm. Full three-dimensional finite-difference time-domain (FDTD) simulations of the Maxwell–Bloch equations confirm the predicted coherent spatiotemporal control.

Generation of injection currents in (110)-oriented GaAs quantum wells: experimental observation and development of a microscopic theory - Bieler, M.; Pierz, K.; Siegner, U.; Dawson, P.; Duc, H. T.; Förstner, Jens; Meier, Torsten (Ultrafast Phenomena in Semiconductors and Nanostructure Materials XIII)
We have experimentally investigated injection currents generated by all-optical excitation of GaAs/AlGaAs quantum wells excited with 130 fs optical pulses. The currents have been detected via free-space THz experiments at room temperature. Our experiments prove that Coulomb effects strongly influence injection currents. This becomes most prominently visible when exciting light-hole exciton transitions. At this photon energy we observe a pronounced phase shift of the current transients which is due to oppositely oriented heavy-hole and light-hole type contributions. We are currently developing a microscopic theory based on a 14×14 k.p model in combination with the semiconductor Bloch equations to describe the observed features quantitatively. The combined theoretical and experimental approach will allow us to analyze the influence of the bandstructure and interaction effects on the injection current amplitude and current dynamics.
Keywords: tet_topic_qw

Determination of homogeneous and inhomogeneous broadenings of quantum-well excitons by 2DFTS: An experiment-theory comparison - Kuznetsova, Irina; Thomas, Peter; Meier, Torsten; Zhang, Tianhao; Cundiff, Steven T. (physica status solidi (c))
The recently developed two-dimensional Fourier-Transform-Spectroscopy (2DFTS) in the optical regime has been established as an elegant experiment, which has manifold of applications in the investigation of semiconductor nanostructures. Here we focus on the real and imaginary part 2DFT spectra. As predicted recently, using rephasing and non-rephasing modes, we are able to determine the homogeneous and inhomogeneous broadenings of coupled excitonic resonances even for weak disorder where photon-echo data are not useful. Computed real and imaginary parts of the 2DFTS for rephasing and non-rephasing modes are compared with experimental data of a GaAs quantum well. It is demonstrated, that phase sensitive data for the rephasing and non-rephasing modes are able to accurately provide the disorder induced broadening in a complex coupled system for each transition separately.

Microscopic analysis of high-harmonic generation in semiconductor nanostructures - Golde, Daniel; Meier, Torsten; Koch, Stephan W. (physica status solidi (c))
A microscopic analysis of the emitted radiation of a semiconductor nanostructure after excitation with an extremely intense ultrashort laser pulse is presented. It is shown that the extreme nonlinear optical response is not sufficiently described by pure interband transitions but one has to include intraband effects as well. Numerical solutions of extended Bloch equations that include the coupled inter- and intraband dynamics are presented. For large excitation intensities, the intraband effects strongly modify the polarization dynamics and lead to a strong enhancement of high-harmonic generation compared to pure interband dynamics.

IMORC: Application Mapping, Monitoring and Optimization for High-Performance Reconfigurable Computing - Schumacher, Tobias; Plessl, Christian; Platzner, Marco (Proc. Int. Symp. on Field-Programmable Custom Computing Machines (FCCM))
Mapping applications that consist of a collection of cores to FPGA accelerators and optimizing their performance is a challenging task in high performance reconfigurable computing. We present IMORC, an architectural template and highly versatile on-chip interconnect. IMORC links provide asynchronous FIFOs and bitwidth conversion which allows for flexibly composing accelerators from cores running at full speed within their own clock domains, thus facilitating the re-use of cores and portability. Further, IMORC inserts performance counters for monitoring runtime data. In this paper, we first introduce the IMORC architectural template and the on-chip interconnect, and then demonstrate IMORC on the example of accelerating the k-th nearest neighbor thinning problem on an XD1000 reconfigurable computing system. Using IMORC's monitoring infrastructure, we gain insights into the data-dependent behavior of the application which, in turn, allow for optimizing the accelerator.
Keywords: IMORC; interconnect; performance

EvoCaches: Application-specific Adaptation of Cache Mapping - Kaufmann, Paul; Plessl, Christian; Platzner, Marco (Proc. NASA/ESA Conference on Adaptive Hardware and Systems (AHS))
In this work we present EvoCache, a novel approach for implementing application-specific caches. The key innovation of EvoCache is to make the function that maps memory addresses from the CPU address space to cache indices programmable. We support arbitrary Boolean mapping functions that are implemented within a small reconfigurable logic fabric. For finding suitable cache mapping functions we rely on techniques from the evolvable hardware domain and utilize an evolutionary optimization procedure. We evaluate the use of EvoCache in an embedded processor for two specific applications (JPEG and BZIP2 compression) with respect to execution time, cache miss rate and energy consumption. We show that the evolvable hardware approach for optimizing the cache functions not only significantly improves the cache performance for the training data used during optimization, but that the evolved mapping functions generalize very well. Compared to a conventional cache architecture, EvoCache applied to test data achieves a reduction in execution time of up to 14.31% for JPEG (10.98% for BZIP2), and in energy consumption by 16.43% for JPEG (10.70% for BZIP2). We also discuss the integration of EvoCache into the operating system and show that the area and delay overheads introduced by EvoCache are acceptable.
Keywords: EvoCache; evolvable hardware; computer architecture

PermaDAQ: A Scientific Instrument for Precision Sensing and Data Recovery in Environmental Extremes - Beutel, Jan; Gruber, Stephan; Hasler, Andi; Lim, Roman; Meier, Andreas; Plessl, Christian; Talzi, Igor; Thiele, Lothar; Tschudin, Christian; Woehrle, Matthias; Yuecel, Mustafa (Proc. Int. Conf. on Information Processing in Sensor Networks (IPSN))
Keywords: WSN; PermaSense

Communication Performance Characterization for Reconfigurable Accelerator Design on the XD1000 - Schumacher, Tobias; Süß, Tim; Plessl, Christian; Platzner, Marco (Proc. Int. Conf. on ReConFigurable Computing and FPGAs (ReConFig))
Keywords: IMORC; graphics

An Accelerator for k-th Nearest Neighbor Thinning Based on the IMORC Infrastructure - Schumacher, Tobias; Plessl, Christian; Platzner, Marco (Proc. Int. Conf. on Field Programmable Logic and Applications (FPL))
Keywords: IMORC; NOC; KNN; accelerator

Woolcano: An Architecture and Tool Flow for Dynamic Instruction Set Extension on Xilinx Virtex-4 FX - Grad, Mariusz; Plessl, Christian (Proc. Int. Conf. on Engineering of Reconfigurable Systems and Algorithms (ERSA))
In this paper, we introduce the Woolcano reconfigurable processor architecture. The architecture is based on the Xilinx Virtex-4 FX FPGA and leverages the Auxiliary Processing Unit (APU) as well as the partial reconfiguration capabilities to provide dynamically reconfigurable custom instructions. We also present a hardware tool flow that automatically translates software functions into custom instructions and a software tool flow that creates binaries using these instructions. While previous research on processors with reconfigurable functional units has been performed predominantly with simulation, the Woolcano architecture allows for exploring dynamic instruction set extension with commercially available hardware. Finally, we present a case study demonstrating a custom floating-point instruction generated with our approach, which achieves a 40x speedup over software-emulated floating-point operations and a 21% speedup over the Xilinx hardware floating-point unit.

Tunable optical properties of photonic crystals and semiconductor microdisks using liquid crystals - Piegdon, Karoline A.; Matthias, Heinrich; Meier, Cedrik; Kitzerow, Heinz-Siegfried (Emerging Liquid Crystal Technologies III)

Erste Ergebnisse zur Messung pädagogischer Kompetenz in der universitären Lehrerausbildung. - Seifert, Andreas; Schaper, Niclas (Tagung „Kompetenzdiagnose und Kompetenzentwicklung in der Lehrerbildung“ des CEVET und PLAZ)

Messung erziehungswissenschaftlicher Kompetenz in der Lehrerausbildung. - Seifert, Andreas; Schaper, Niclas; Hilligus, Annegret Helen; Grafe, Silke (AEPF-Tagung „Kompetenz – Modellierung – Diagnostik – Entwicklung – Förderung“)

High harmonics generated in semiconductor nanostructures by the coupled dynamics of optical inter- and intraband excitations - Golde, D.; Meier, Torsten; Koch, S. W. (Physical Review B)
The emitted radiation from semiconductor nanostructures due to the excitation with intense ultrashort optical laser pulses is analyzed. Semiconductor Bloch equations that consistently describe the coupled light-field-induced interband and intraband dynamics are solved numerically. It is demonstrated that the intraband dynamics considerably influences the light emission in the regime of extreme nonlinear optics. In particular, the intraband acceleration significantly modifies the dynamics of the interband polarization which results in a strong enhancement of high-harmonic generation.

Generation and Time-Resolved Detection of Coherently Controlled Electric Currents at Surfaces - Güdde, J.; Rohleder, M.; Meier, Torsten; Koch, S.W.; Höfer, U. (Frontiers in Optics 2008/Laser Science XXIV/Plasmonics and Metamaterials/Optical Fabrication and Testing)

Rabi flopping of charge and spin currents generated by ultrafast two-colour photoexcitation of semiconductor quantum wells - Pasenow, B.; Duc, H.T.; Meier, Torsten; Koch, S.W. (Solid State Communications)
Keywords: Materials Chemistry; Condensed Matter Physics; General Chemistry

EvAnT: Analysis and Checking of event traces for Wireless Sensor Networks - Woehrle, Matthias; Plessl, Christian; Lim, Roman; Beutel, Jan; Thiele, Lothar (IEEE Int. Conf. on Sensor Networks, Ubiquitous, and Trustworthy Computing (SUTC))
Keywords: WSN; testing; verification

A Hardware Accelerator for k-th Nearest Neighbor Thinning - Schumacher, Tobias; Meiche, Robert; Kaufmann, Paul; Lübbers, Enno; Plessl, Christian; Platzner, Marco (Proc. Int. Conf. on Engineering of Reconfigurable Systems and Algorithms (ERSA))

IMORC: An infrastructure for performance monitoring and optimization of reconfigurable computers - Schumacher, Tobias; Plessl, Christian; Platzner, Marco (Many-core and Reconfigurable Supercomputing Conference (MRSC))
Keywords: IMORC; IP core; interconnect

Vorausschau ind Technologieplanung. 4. Symposium für Vorausschau und Technologieplanung Heinz Nixdorf Institut, 30. und 31. Oktober 2008 - Gausemeier, Jürgen

Tuneable photonic crystals obtained by liquid crystal infiltration - Kitzerow, Heinz-Siegfried; Lorenz, A.; Matthias, H. (physica status solidi (a))
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Liquid crystal director fields in micropores of photonic crystals - Matthias, Heinrich; Schweizer, Stefan L; Wehrspohn, Ralf B; Kitzerow, Heinz-Siegfried (Journal of Optics A: Pure and Applied Optics)
Keywords: Atomic and Molecular Physics; and Optics

Gefährlichkeitseinschätzung von Autofahrern, Motorradfahrern und Radfahrern. Psychometrische Modellierung der Prognose durch verschiedene Gefahrenaspekte und ihr Beitrag zur Klärung von Unterschieden zwischen jungen und nicht-jungen Verkehrsteilnehmern. - Seifert, Andreas

Time-Resolved Investigation of Coherently Controlled Electric Currents at a Metal Surface - Gudde, J.; Rohleder, M.; Meier, Torsten; Koch, S. W.; Hofer, U. (Science)
Studies of current dynamics in solids have been hindered by insufficiently brief trigger signals and electronic detection speeds. By combining a coherent control scheme with photoelectron spectroscopy, we generated and detected lateral electron currents at a metal surface on a femtosecond time scale with a contact-free experimental setup. We used coherent optical excitation at the light frequencies ωa and ωa/2 to induce the current, whose direction was controlled by the relative phase between the phase-locked laser excitation pulses. Time- and angle-resolved photoelectron spectroscopy afforded a direct image of the momentum distribution of the excited electrons as a function of time. For the first (n = 1) image-potential state of Cu(100), we found a decay time of 10 femtoseconds, attributable to electron scattering with steps and surface defects.

Polarization-dependent optical 2D Fourier transform spectroscopy of semiconductors - Zhang, T.; Kuznetsova, I.; Meier, Torsten; Li, X.; Mirin, R. P.; Thomas, P.; Cundiff, S. T. (Proceedings of the National Academy of Sciences (PNAS))
Optical 2D Fourier transform spectroscopy (2DFTS) provides insight into the many-body interactions in direct gap semiconductors by separating the contributions to the coherent nonlinear optical response. We demonstrate these features of optical 2DFTS by studying the heavy-hole and light-hole excitonic resonances in a gallium arsenide quantum well at low temperature. Varying the polarization of the incident beams exploits selection rules to achieve further separation. Calculations using a full many-body theory agree well with experimental results and unambiguously demonstrate the dominance of many-body physics.

Increasing the Reliability of Wireless Sensor Networks with a Distributed Testing Framework - Woehrle, Matthias; Plessl, Christian; Beutel, Jan; Thiele, Lothar (Proc. Workshop on Embedded Networked Sensors (EmNets))
Keywords: WSN; testing; distributed; embedded

Automated Wireless Sensor Network Testing - Beutel, Jan; Dyer, Matthias; Lim, Roman; Plessl, Christian; Woehrle, Matthias; Yuecel, Mustafa; Thiele, Lothar (Proc. Int. Conf. Networked Sensing Systems (INSS))
Keywords: WSN; testing; verification

Der Vielfalt begegnen – Die Arbeit an der Lerntheke als eine Möglichkeit der inneren Differenzierung im Mathematikunterricht - Aschhoff-Hartmann, Stefanie (Zeitschrift für Heilpädagogik)

Ein mehrbenutzerfähiges Werkzeug zur Modellierung und richtungsoffenen Simulation von wahlweise objekt- und funktionsorientiert gegliederten Fertigungssystemen - Laroque, C.

Zellen-basiert Dienst-Entdeckung für Roboternetzwerke - Du, J.

Optical Experiments on Second-Harmonic Generation with Metamaterials Composed of Split-Ring Resonators - Klein, Matthias W.; Enkrich, Christian; Wegener, Martin; Förstner, Jens; Moloney, Jerome V.; Hoyer, Walter; Stroucken, Tineke; Meier, Torsten; Koch, Stephan W.; Linden, Stefan (Photonic Metamaterials: From Random to Periodic)
We study optical second-harmonic generation from planar arrays of magnetic split-ring resonators at 1.5 microns resonance wavelength. We obtain by far the largest signals when exciting the magnetic-dipole resonance.
Keywords: tet_topic_meta

Microscopic analysis of extreme nonlinear optics in semiconductor nanostructures - Golde, Daniel; Meier, Torsten; Koch, Stephan W. (Journal of the Optical Society of America B)
A microscopic analysis is presented for the extreme nonlinear optical response of semiconductor quantum wells and wires after intense excitation with femtosecond laser pulses. In this regime, the light–matter interaction is the dominant eneregy scale, leading to a number of interesting effects such as carrier-wave Rabi flopping, Mollow splitting, and the creation of higher harmonics. The results presented here were obtained by evaluating the semiconductor Bloch equations without the rotating wave approximation. The electronic dispersion of semiconductor nanostructures is shown to have a characteristic influence on the extreme nonlinear optical response, whereas the relative importance of the carrier Coulomb interaction decreases with increasing excitation intensities.

Characterization of Disorder in Semiconductors via Single-Photon Interferometry - Bozsoki, P.; Thomas, P.; Kira, M.; Hoyer, W.; Meier, Torsten; Koch, S. W.; Maschke, K.; Varga, I.; Stolz, H. (Physical Review Letters)
The method of angular photonic correlations of spontaneous emission is introduced as an experimental, purely optical scheme to characterize disorder in semiconductor nanostructures. The theoretical expression for the angular correlations is derived and numerically evaluated for a model system. The results demonstrate how the proposed experimental method yields direct information about the spatial distribution of the relevant states and thus on the disorder present in the system.

Microscopic modeling of the optical properties of semiconductor nanostructures - Thränhardt, A.; Meier, Torsten; Reichelt, Matthias; Schlichenmaier, C.; Pasenow, B.; Kuznetsova, I.; Becker, S.; Stroucken, T.; Hader, J.; Zakharian, A.R.; Moloney, J.V.; Chow, W.W.; et al. (Journal of Non-Crystalline Solids)
A brief overview of a consistent microscopic approach to model the optical and electronic properties of semiconductor nanostructures is presented. Coupled semiconductor Bloch and Maxwell equations are used to investigate the performance of semiconductor microcavity structures, photonic band gap systems, and lasers. The predictive potential of the microscopic theory is demonstrated for several examples of practical importance. Optical gain and output characteristics are computed for modern vertical external cavity surface emitting laser structures. It is shown how design flexibilities can be used to optimize the device performance. Nanostructures are proposed where semiconductor quantum wells are embedded in one-dimensional photonic crystals. For field modes spectrally below the photonic band edge it is shown that the optical gain and absorption can be enhanced by more than one order of magnitude over the value of the homogeneous medium. The increased gain can be used for laser action by placing quantum wells and a suitably designed photonic crystal structure inside a microcavity.

Temporal decay of coherently optically injected charge and spin currents due to carrier–LO-phonon and carrier-carrier scattering - Duc, H. T.; Vu, Q. T.; Meier, Torsten; Haug, H.; Koch, S. W. (Physical Review B)
The coherent ultrafast optical injection and the temporal evolution of charge and spin currents in semiconductors is analyzed using a microscopic many-body theory. The approach is based on the semiconductor Bloch equations and includes light-field-induced intraband and interband excitations, excitonic effects, and carrier–LO-phonon and carrier-carrier scattering processes. The relaxation effects are treated both in the second Born-Markov approximation and on the level of quantum kinetic theory including memory effects. The dynamics of the charge and spin currents is evaluated numerically for a one-dimensional model system. The dependence of the currents and their decay on the temperature, the excitation intensities, and the frequencies of the incident light fields is discussed. Whereas the overall decay dynamics is described well within the Markov approximation, the quantum kinetic theory predicts additional oscillatory signatures in the current transients.

Mode Locking of Electron Spin Coherences in Singly Charged Quantum Dots - Greilich, A.; Yakovlev, D. R.; Shabaev, A.; Efros, Al. L.; Yugova, I. A.; Oulton, R.; Stavarache, V.; Reuter, Dirk; Wieck, A.; Bayer, M. (Science)
The fast dephasing of electron spins in an ensemble of quantum dots is detrimental for applications in quantum information processing. We show here that dephasing can be overcome by using a periodic train of light pulses to synchronize the phases of the precessing spins, and we demonstrate this effect in an ensemble of singly charged (In,Ga)As/GaAs quantum dots. This mode locking leads to constructive interference of contributions to Faraday rotation and presents potential applications based on robust quantum coherence within an ensemble of dots.
Keywords: Multidisciplinary